Trachoma: an underdiagnosed disease revealed by a survey carried out at Jaú, São Paulo - Schaal, Luisa Fioravanti [UNESP]; Meneghim, Roberta Lilian Fernandes de Sousa [UNESP]; Ferraz, Lucieni Cristina Barbarini; Padovani, Carlos Roberto [UNESP]; Victoria, Cassiano [UNESP]; Schellini, Silvana Artioli [UNESP] (Springer Nature, 2024)
Background: Trachoma is a notifiable disease in the state of São Paulo– Brazil. However, in Jaú, a municipality located in this state, in the last 10 years there are no records of cases. This study purpose is to assess if there are cases of inflammatory trachoma in schoolchildren aged 1 to 9 years in the municipality of Jaú as well if it is possible to detect clusters areas of the disease to establish elimination programs. Methods: An epidemiological study was performed in 2018, involving a stratified random sample of schoolchildren aged 1- to 9-year-old, from public day care centers and elementary schools in the municipality of Jaú. A trachoma screening following the criteria of the World Health Organization (WHO) and the distribution of cases was assessed using geoprocessing. Results: Four thousand-six hundred-nineteen children from 44 elementary schools were examined, and 126 children with active trachoma were detected, with an adjusted prevalence rate of 2.65%. The prevalence was higher (3.01%) in children aged 6- to 9-year-old compared to children aged 1-to 5-year-old (2.42%). There were clusters with a higher concentration of positive cases of the disease in three schools located in the neighborhoods with lower socioeconomic conditions. Conclusion: Inflammatory trachoma still present in children aged 1- to 9-year-old in the city of Jaú. The positive cases were located mainly in areas with low socioeconomic conditions. Health promotion with active search and periodical treatment must be planned to fight this important blinding cause, that persists in our municipality.
Keywords: Brazil; Epidemiology surveys; Prevalence; Trachoma